UPAYA PEMULIHAN PASCA GEMPA BUMI PASAMAN BARAT DI NAGARI MALAMPAH KECAMATAN TIGO NAGARI KABUPATEN PASAMAN - Kifli, Kifli; Ernawati, Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
The aim of this research is to find out how the government has attempted to recover after the West Pasaman Earthquake Disaster in Jorong Siparayo, Nagari Malampah, Tigo Nagari District, Pasaman Regency. Knowing the Impact of Earthquake Natural Disasters. This research uses quantitative descriptive methods. Where sampling uses purposive sampling, because it is suitable for quantitative research, or research that does not use generalizations. This research used a sample of the entire Malampah community, totaling 9,117 people. This research focuses on one jorong, namely Jorong Siparayo, the number of samples in this study is 87. Based on the results of the research, it can be concluded that the government's efforts in post-earthquake recovery such as Reconstruction and Rehabilitation of Settlements, namely the construction of temporary shelters are relatively high, because they get a percentage of 64% .